UTICAJ ADMINISTRATIVNIH BARIJERA NA POSLOVANJE PREDUZEĆA: EMPIRIJSKA STUDIJA U REPUBLICI SRPSKOJ - Zoran Lukić; Predrag Đurić; Boris Novarlić (Zbornik Radova Ekonomskog Fakulteta u Istočnom Sarajevu, 2014)
A relatively long period of economic crisis, inflexible institutional and regulatory framework and inadequate economic policy are features of the national economy of the Republic of Srpska which have resulted in less rapid revival of the economy, as compared to the surrounding countries. Enterprises are faced with unfavourable business environment mostly accompanied with complex, long and expensive administrative procedures. In total of the observed sample, 41% of companies believe that administrative procedures of the municipal/city are complicated, while 44% of them have the same opinion about the respective government institutions. In addition, 43% of the observed sampled companies think that the municipal/city procedures are time-consuming, while 41% of them share the same opinion about the government institutions. Starting from the above mentioned circumstances, the research made within this theoretical-empirical study is based on finding appropriate solutions in terms of eliminating the negative impact of administrative barriers for the business enterprises, with special emphasis on small and medium sized enterprises. Defining the project model of organizational structure, especially the segment that refers to the way of successful business enterprise, as well as its performance, also determines pragmatic contribution of this paper with recommendations for further research.